Differential diagnosis of diarrhea Beitrag zur differenzialdiagnostik der diarrhö - Vieth, M.; Neumann, Helmut (Verdauungskrankheiten, 2012)
Diarrhea is one of the most common causes of death in developing countries and symptom of various gastrointestinal diseases including inflammatory bowel disease, microscopic colitis, infectious colitis and congenital enzyme defects. Diagnosis includes clinical, endoscopic and histologic data. In this review we focus on different types of diarrhea, their diagnosis and respective therapy. © 2012. Dustri-Verlag Dr.Karl Feistle.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Diarrhoe; Endoscopy; Histology; IBD; Microscopic colitis